Supporting systems transformation through design‐driven evaluation. Issue 170 (1st September 2021) - Norman, Cameron D.
Abstract: As complexity in human social‐technical systems grows so does the need to provide useable guidance for how to effectively create change within them. A design‐driven approach to evaluation draws on lessons from complexity science and incorporates service and product design knowledge into the process of creating and implementing new knowledge or actions into a setting to produce value (innovation). This article introduces the fundamental tenets of a design‐driven evaluation (DDE) approach and illustrates its use in developing frameworks for evaluation that can support innovation and program development. Drawing on the science of systems and their application to evaluation, Developmental and Principles‐focused Evaluation, and systems‐oriented design theory and practice, a model for innovation development is proposed that will reframe program evaluation as both a service and product to aid system change.